(3cGed GdUfGYJjf GdHjWQI hGdRQObIs - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s ((3eMeO Hf eMeO GdHMjQi s)
(3ChdgG (B:s
(3aCMHHJ Cf CLeY dNRGfJg cJGHkG cGedkG TGajkG dLejY eG jMJGL Edjg ef GQGO Yde GdHjWQI hGdRQObI s
(3BNQgG (B:s
(3hGdKGfi (B: (3dCfg de jcf dgG efaYI ai GdJfYjd hOaY GdeVGQ hdcfgG ddJaGNQ Hjf GdHjGWQI hGdUfGY s
(3CMO GdHjGWQI HGSWHdGJ Gdedc GdfGUQ eMeO Hf bdGhhfs
(3fSNI NRGFfjI eTchdI HQSe (B" (3GdLfGH GdYGdi Gdehdhi GdCejQi GdcHjQi GdeMJQei GdeNOhei CbHGi HhGH GdSdWfg GdTQjag (B" (3HgG QShe GdNdjd hYdGeGJ Gdcis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B76s
Keywords: (3GdWHs